Return to Face-to-Face Classrooms in Higher Education: Students Experiences in Chile, Venezuela, and Ecuador - Karla Lobos; Rubia Cobo-Rendón; Fabiola Sáez; Javier Mella; Nataly Cisternas (Emerging Science Journal, 2023)
Emergency remote teaching (ERE) triggered by the COVID-19 pandemic posed significant challenges to higher education institutions worldwide. Although it had several negative consequences, it also enabled advances in the integration of technology into the teaching and learning process. The purpose of this study was to examine and characterize the key elements of the process of returning to face-to-face courses. The study was based on a mixed quantitative and qualitative design. 631 students from Chile, Venezuela, and Colombia were surveyed about their experiences returning to face-to-face classes (in terms of virtual tools, their feelings, and their expectations for academic success). The survey also included questions about the lockdown caused by the pandemic, specifically regarding instructional and didactic design, participation in online sessions, and the role of faculty during the pandemic. Descriptive and correlative analyses were performed to examine relationships among variables. Qualitative data were analyzed within a hermeneutically-oriented framework. Our analyses show that virtual classrooms or learning management systems (LMS) continued to be used after the pandemic. However, their use is strongly associated with a more traditional approach to teaching; LMSs and virtual classrooms are primarily used as filing locations and for receiving and storing homework assignments and assessments. In terms of interaction, qualitative analyses have shown that relationships with faculty and between students are better in face-to-face classes and that there is not much difference in perceptions of collaborative work in online learning compared to face-to-face classes. Finally, students' expectations of academic success are low in the short term, while they are higher in the long term. Students also indicated that it is important to them that teachers take care about the didactic design of the course, including strategies that encourage interaction and participation in both synchronous and asynchronous sessions. In addition, students mentioned that teachers should incorporate strategies to promote academic motivation, self-regulation, and a safe environment. An important finding of this study is that students prefer a blended learning format when comparing online and face-to-face instruction. This article also provides recommendations for the new post-pandemic education scenario. Doi: 10.28991/ESJ-2023-SIED2-017 Full Text: PDF